Dampak Perkebunan Kelapa Sawit terhadap Lingkungan:Menyeimbangkan Risiko Ekologis dengan Keuntungan Ekonomi - Muhammad Riyan Hidayah (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Particularly in tropical nations like Indonesia and Malaysia, oil palm plantations have grown to be a significant economic sector worldwide. Although these plantations offer substantial economic advantages, there are a number of environmental effects associated with their growth that must be taken into account. The ecological effects of oil palm plantations, such as deforestation, biodiversity loss, greenhouse gas emissions, and air and land pollution, are covered in this article. It also covers mitigation techniques, such the use of sustainable farming methods, ecosystem poisoning, and ecosystem restoration, to strike a balance between financial gains and environmental extinction. Without compromising its financial gains, the palm oil sector may grow in a more ecologically responsible way with the correct strategy.